ARTISTIC AND GRAPHIC DESIGN OF ADVERTISEMENTS OF THE LATE XIX – EARLY XX CENTURY (BASED ON THE MATERIALS OF THE KYIV CALENDARS) - Krotova, T. F.; Osadcha, A. M.; Struminska, T. V.; Ryabinova, I. M. (Art and Design, 2021)
Aim: to explore the means of artistic and graphic design of advertisements in periodicals of the late nineteenth – early twentieth century. Methodology. The historical, analytical, iconographic methods have been used in the research; the methods of formal, figurative-stylistic, and comparative analysis have been used for analyzing the samples of advertisements. Results. The analysis of advertisements of periodicals "Kyiv Calendar" of 1989 and "Kyiv Zemsky Calendar and reference book for 1911" is presented in the work in terms of artistic and graphic means (composition, fonts, stylistic features of fonts, images, the nature of images, graphic decorative elements) and terms of tools influencing consumer motivation. Advertisers have been found to use a variety of fonts, highlighting company and institution names, creating messages with textual information only, and combining text with an image to give a potential customer an associative view of the product. Logos and trademarks in this period in the published messages are almost not observed, the companies provided information with the name of the product, the name of the owner, and address. Scientific novelty. Abilities of print advertising at the end of XIX – the beginning of the XX centuries have been analyzed, the means of artistic and graphic design of advertisements and tools of influencing motivation of potential consumers have been revealed. Practical significance. The revealed peculiarities of artistic and graphic design of advertisements in periodicals of the end of XIX – beginning of XX centuries based on the materials of the Kyiv calendars provide an idea of the approaches and capabilities of artists and printing houses in creating advertising forms for the promotion of goods and services in the market. The analyzed samples of advertising introduce the variety, names, and characteristics of goods and services of the analyzed period.